“I Could Hardly Breathe”: Teachers’ Lived Experiences of Bereavement After the Violent Death of a Student - Arksey, Aleigha M.; Greidanus, Elaine J. (Canadian Journal of Counselling and Psychotherapy, 2022)
Teachers’ bereavement experiences after the violent death of a student consist of an area that warrants more study, given the increased risk of experiencing persistent complex bereavement due to the traumatic nature of violent deaths. A phenomenological methodology was adopted to explore teachers’ experiences after the violent death of one or more of their students. Interviewing five participants revealed that such experiences are both personal and professional. Students and teachers can form strong, long-lasting bonds that act as the foundation for understanding the bereavement experienced when students die. Participants identified several barriers that can arise when seeking help. Collegial support was reported to be important for teachers’ journeys of healing. In regards to counselling, teachers’ needs immediately following such a loss may differ from ongoing counselling needs. Follow-up counselling support (utilizing a trauma and bereavement lens), targeted 1 or more years after the loss, may be more important than previously considered.